Treatment of food waste from a university restaurant added to sugarcane bagasse - Rizk, M. C. [UNESP]; Bonalumi, I. P. [UNESP]; Almeida, T. S. [UNESP]; Camacho, F. P.; Vilarinho, C.; Castro, F.; Lopes, M. D. (Crc Press-taylor & Francis Group, 2018)
Restaurants produce large-scale meals, generating large amounts of solid waste, which if not properly managed cause environmental and sanitary problems. Composting is one of the most recommended methods for the treatment of organic solid waste, since the wastes that would be disposed off in the environment, causing environmental and public health problems, are transformed into organic fertilizers. Thus, the present study had the objective of monitoring some physical-chemical parameters of the composting process of food waste from a university restaurant mixed to the sugarcane bagasse. The final values indicated that the moisture content is above that determined in the legislation, while the pH and the C/N ratio presented values very close to the reference values. In this way, it's concluded that it is necessary more time of composting to adjust some parameters, so it will be possible to obtain an organic compost suitable for use in soil.